Fragment or the borderlands of philosophy and literature in Emil Cioran’s writings - Szaj, Patryk (Hybris, 2014)
This article concerns fragmentary writing of Emil Cioran. The author tries to show that the fragment is a specific type of artistic creativity that is situated between literature and philosophy. The initial part of the article deals with the problem of modern fragmentarism that was born in the times of German romanticism. Then, the author investigates the causes of Cioran’s fragmentary writing, which are: the opposition to systematic philosophy, the opposition to modern idea of a literary „work” and the intellectual honesty which shows heterogeneity of life. All this makes the fragment very difficult to interpret: we wish to adopt the whole sense of it, but we cannot do this. Also, the title issue turns out to be unsolvable. Cioran escapes fixed categories. And fragment, as an unsuccessful, fractured discourse, can be both literature and philosophy, or none of them. That makes it similar to Jacques Derrida’s ideas of farmakon, aporia or différance.